THE EFFECT OF INTERNAL CONTROL SYSTEM ON THE MANAGEMENT AND ACCEPTANCE SYSTEM OF INDONESIA SMART PROGRAM (PIP) IN MAN 1 BOYOLALI 2020-2021 - Muslikah Muslikah; LMS Kristiyanti; Rukmini Rukmini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: The purpose of this research was to determine the effect of the Internal Control System on the Management and Acceptance System for the Smart Indonesia Program (PIP) at MAN 1 Boyolali. The type of research uses quantitative methods. Data collection techniques using questionnaires. The data measurement scale with Likert scale. Data were analyzed using simple linear regression analysis with the help of SPSS program. The results of the coefficient of determination test show that 51.6% is influenced by the Implementation of the Internal Control System on PIP Management and Recipients, while the remaining 48.8% is influenced by other variables not included in this research model. Thus it can be concluded that the Internal Control System contributes to the Management and Receipt of PIP funds at MAN 1 Boyolali.